Participação das vesículas extracelulares de leveduras de Sporothrix brasiliensis na resposta imune da Esporotricose: estudo ex vivo e in vivo - Ikeda, Marcelo Augusto Kazuo [UNIFESP] (2018)
Sporotrichosis is a mycotic emerging infectious disease, it affects the skin, lymphatic system, and other organs from humans and animals. The fungus infection has a worldwide distribution and is endemic in areas from Brazil. The disease is caused by the complex of at least four pathogenic species, including Sporothrix brasiliensis. Some fungi release extracelullar vesicles (EVs) to transport molecules, that can interact with the host cell and modulate the immune response. The aim of the study is analyze the participation of the EVs from S. brasiliensis yeasts in the immune response of dendritic cells (DCs) and in murine model. EVs were obtained by differential centrifugation from the supernatant of S. brasiliensis yeast culture. Bone marrow derived DCs were stimulated for 30 minutes with the EVs and then cocultured with yeasts. After 4 hours we analyzed the phagocytic index and after 24 hours the fungal burden. Also, we inoculated the EVs in BALB/c mice before an subcutaneous infection with the fungi, and observed the diameter and fungal burden from the lesion after 21, 35 and 42 days. Our results showed that how much more EVs in the culture higher is the phagocytic index in DCs after 4 hours. However, we observed an increase of the fungal burden after 24 hours of infection. In the murine model, the inoculation of the EVs increased the fungal burden and the diameter of the lesion after 21 days. However, after 35 days, we observed a regression of the lesion, that persists until 42 days after infection. Also, an 100 kD component from EVs reacts with serum from infected animals, and when we analyzed the characterized proteins, we observed some proteins that could be involved in virulence, as WD40 protein, heat shock protein, major facilitator superfamily transporter, extracellular cell wall glucanase, carbonic anhydrase and a mitogen activated protein kinase. These results suggest that EVs can have an important role in virulence and modulation of experimental S. brasiliensis infection.